1979
DOI: 10.1103/physrevb.19.3004
|View full text |Cite
|
Sign up to set email alerts
|

Soft-x-ray-induced secondary-electron emission from semiconductors and insulators: Models and measurements

Abstract: Secondary-electron energy distribution curves (EDC's) and the total secondary-electron yields relative to such for gold have been measured for seven semiconductors for which electron-electron scattering losses within the emitter were considered dominant and for nine insulators (alkali halides) for which electronphonon scattering losses were expected to be dominant in the transport process. The secondary-electron spectra were excited by Al-Ka (1487 eV) photons and were measured from evaporated dielectric films … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

8
91
0

Year Published

1991
1991
2018
2018

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 220 publications
(99 citation statements)
references
References 42 publications
8
91
0
Order By: Relevance
“…Still missing in our approach is a proper treatment of the low-energy regime, where phonon scattering becomes significant for the energy loss of the SEs. 20,22,26 Since our main objective is to compare the characteristics of the electron cascades generated in KI and CsI, we have, for the sake of simplicity, not included the treatment of holes. The average electron-hole pair creation energy is given by the ratio between the energy deposited in the system and the total number of SEs generated.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Still missing in our approach is a proper treatment of the low-energy regime, where phonon scattering becomes significant for the energy loss of the SEs. 20,22,26 Since our main objective is to compare the characteristics of the electron cascades generated in KI and CsI, we have, for the sake of simplicity, not included the treatment of holes. The average electron-hole pair creation energy is given by the ratio between the energy deposited in the system and the total number of SEs generated.…”
Section: Resultsmentioning
confidence: 99%
“…[18][19][20] Kane 21 presented a first derivation for the rate of inelastic scattering of electrons by considering the production of electronhole pairs in silicon. Henke et al 22 performed further investigations for semiconductors and insulators as compared to gold, both theoretically and experimentally, with respect to the electrons' total yield and their distribution in energy. In their model they accounted for both electron and phonon scattering, but worked under a free-electron band description and thus did not fully treat the bound nature of the collective excitations.…”
Section: Introductionmentioning
confidence: 99%
“…[8][9][10][11] These and more recent [12][13][14][15][16][17][18] studies have not yet been able to provide a complete and coherent account of all observed phenomena. This could be due to the prevailing emphasis on static (stationary) models [19][20][21] rather than time-domain analysis. Studying the dynamics of charging in time domain is especially important in the analysis of response times in particle detectors 2 and in designing novel scanning strategies for SEM.…”
Section: Introductionmentioning
confidence: 99%
“…Figure 2 shows results of x-ray calibrations of the LIL XSC#5 equipped successively with hard (5000 Å lexan/260 Å Al/ 2400 Å CsI) and soft x-ray photocathodes (1000 Å lexan/260 Å Al/ 2400 Å CsI). Measurements are compared to a modified transmission Henke's model [2][3][4] and are in a relatively good agreement. Relative uncertainties achieved thanks to our transposition system and collimation system calibration range henceforth from 7 to 9% k=2 (squared plots on figure 3).…”
Section: X-ray Streak Cameras (Xsc)mentioning
confidence: 99%
“…The same calibrated visible CCD is used to record visible emission coming from the phosphor screen. Figure 4 shows an example of yield calibration for these 13004-p. 3 cameras. Experimental data are compared to both CEA-DIF's work and one XFC model we developed which simulates the behaviour of MCP and phosphor screen in the calibration experimental conditions.…”
Section: X-ray Framing Camera (Xfc)mentioning
confidence: 99%